Higher Education and Post-Conflict Recovery - Milton, Sansom (Springer International Publishing, 2018)
This book offers a critical review of higher education and post-conflict recovery. It provides the first systematic study with a global scope that investigates the role of higher education systems in conflict-affected and fragile contexts. The first part of the book analyses the long-standing neglect of higher education in post-conflict recovery, the impact that conflict can have on the sector, and efforts to rebuild and reform higher education systems affected by violent conflict. The second part of the book considers the positive and negative contributions that higher education can make to a range of areas of recovery including humanitarian action, forced displacement, post-conflict reconstruction, statebuilding, and peacebuilding. With its reasoned defence of the importance of higher education for post-conflict recovery, the book will be of appeal to researchers, university students, and humanitarian and development policy-makers and practitioners. .